ANALISIS PESAN DAKWAH DALAM LAGU SIAPA YANG MENCIPTAKAN DARI ANIMASI RIKO THE SERIES - Hidayat, Tatang; Haslam, Desy Sapitri; Istianah, Istianah (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2024)
This study aims to determine the da'wah message contained in the song Who Created from the animation Riko The Series. This research uses a qualitative method that emphasizes the discovery of meaning, using content analysis, analyzing lyrics and video visuals to identify the main themes of da'wah messages. The data source of this research is the video of the song